UPAYA MENINGKATAN KEPERCAYAAN DIRI ANAK USIA MELALUI KEGIATAN MENJURNAL DI TKIT NUSANTARA BANTEN - Siti Erma Maemunah; Sella Oktania (Jurnal Anak Bangsa, 2023)
The purpose of this study was to find out the process of implementing journaling activities to increase the self-confidence of group B children at TKIT Nusantara Banten. This study uses the Kemmis and Mc Taggart model of action research. The subjects in this study were the children of Group B TKIT Nusantara Banten. This research was conducted in two cycles, the first cycle consisted of eight meetings and the second cycle consisted of four meetings. Data analysis in this study used qualitative and quantitative. Quantitative analysis uses descriptive statistics to compare the results in the first cycle and the second cycle. Qualitative data analysis by analyzing data from field notes and interviews during the study with data reduction, data display and data verification steps. The results of this study indicate that self-confidence through journaling activities increases well. This can be seen from the success of each research cycle, where the results obtained in the pre-cycle were 46.30%, cycle I was 62.85% and in cycle II the confidence reached 82.52%. From the results found, the implication of this research is that journaling activities can be used as an alternative approach to increase children's self-confidence